Application of multilocus enzyme electrophoresis in studies of the epidemiology of Listeria monocytogenes in Denmark. - Nørrung, B (1993)
A total of 245 strains of Listeria monocytogenes were investigated. These strains were isolated from human and animal cases of listeriosis as well as from different kinds of raw and processed foods. Thirty-three electrophoretic types (ETs) were identified among the 245 strains. The strains investigated included all human clinical strains isolated in Denmark during 1989 and 1990. Seventy-three percent of the strains isolated in this period were assigned to one of only two ETs (ET 1 and ET 4). ET 1, which was found to be the most frequently occurring ET among strains isolated from human clinical cases, was also found to occur rather frequently in animal clinical cases. ET 1 was, however, found only sporadically among strains isolated from foods and food factories. The data indicate that there might be something distinctive about the physiology or ecology of the ET 1 clone which makes it more likely to bring about disease in human beings either because of high pathogenicity or because of a special ability to multiply to infectious doses in processed foods. Another type, designated ET 4, was found to be the next most frequently occurring ET, after ET 1, among human clinical isolates. This could be explained by the fact that ET 4 was found to be the most frequently occurring ET within food isolates.